2017
DOI: 10.1002/slct.201601658
|View full text |Cite
|
Sign up to set email alerts
|

Effective Hydrodeoxygenation of Stearic Acid and Cyperus Esculentus Oil into Liquid Alkanes over Nitrogen‐Modified Carbon Nanotube‐Supported Ruthenium Catalysts

Abstract: Nitrogen-modified carbon nanotube-supported ruthenium catalyst was demonstrated to be effective in the conversion of crude cyperus esculentus oil into linear liquid alkanes. The model compound stearic acid was nearly quantitatively converted into liquid alkanes, and the yields of n-heptadecane and n-octadecane were 89.5 % and 8.5 %, respectively. The mass yield of liquid alkanes from crude cyperus esculentus oil was 76.6 %, which was very close to the theoretical yield. The catalyst could be reused at least si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(4 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…To date, FAME has been synthesized by a variety of basic (and sometimes acid) catalysts, including our polymeric acid catalyst. However, since the stability and combustibility of FAME are poorer than thaose of BHD, the development of suitable catalysts for the efficient production of BHD is of particular importance in the context of renewable energy sources. In this context, a number of homogeneous and heterogeneous catalysts have been reported. For example, Vardon et al reported that the decarboxylation of stearic acid using a Pt–Re/C catalyst resulted in the highly selective formation of C 17 alkanes, while Kaneda et al and Zhang et al reported the decarboxylation of fatty acids using Ru-CeO 2 and Ru-HAP catalysts, respectively, to yield BHD. However, the development of highly active, reusable, and selective supported catalysts for BHD production remains a challenge.…”
Section: Introductionmentioning
confidence: 99%
“…To date, FAME has been synthesized by a variety of basic (and sometimes acid) catalysts, including our polymeric acid catalyst. However, since the stability and combustibility of FAME are poorer than thaose of BHD, the development of suitable catalysts for the efficient production of BHD is of particular importance in the context of renewable energy sources. In this context, a number of homogeneous and heterogeneous catalysts have been reported. For example, Vardon et al reported that the decarboxylation of stearic acid using a Pt–Re/C catalyst resulted in the highly selective formation of C 17 alkanes, while Kaneda et al and Zhang et al reported the decarboxylation of fatty acids using Ru-CeO 2 and Ru-HAP catalysts, respectively, to yield BHD. However, the development of highly active, reusable, and selective supported catalysts for BHD production remains a challenge.…”
Section: Introductionmentioning
confidence: 99%
“…To confirm the chemical adsorption of stearic acid on the Fe-N-C@Al 2 O 3 -900 catalyst surface, the treated catalyst was prepared as in our previous studies. 46 A 0.1 g portion of Fe-N-C@Al 2 O 3 -900 catalyst was added to 20 mL of a 0.05 M nhexane solution of stearic acid, and the mixture was stirred at room temperature for 12 h. Then the solid was separated by centrifugation by washing it 15 times with n-hexane. The residue was dried at 80 °C overnight under N 2 .…”
Section: Introductionmentioning
confidence: 99%
“…117,121 These heteroatoms alter the electronic structure, increase the selective adsorption of reactants, enhance metal and carrier interactions, increase the structural defects of the support and are expected to tune the reaction path, contributing to the increased activity of the catalyst. [122][123][124] The catalytic activity and product selectivity in various catalytic reactions due to the heteroatom doping engineering of carbon-based catalysts is illustrated in Table 4. Liu et al 125 fabricated a two-site separated nanoreactor for the hydrogenation of levulinic acid (LA) in water consisting of double-shelled hollow carbon spheres (DSC) supported by a precise distribution of nitrogen in the outer shell, while ultrane Ru nanoparticles were encapsulated in a hollow sandwich (Fig.…”
Section: Spatial Compartmentation Effect For Multifunctional Optimiza...mentioning
confidence: 99%